“Implementación de un módulo didáctico de control de dos variables de proceso (caudal y presión), para el área de Instrumentación Industrial”. - Chimborazo Aguaisa, Widinson Alexander (2022)
The control and automation of industrial processes allow industries to improve their production and to have greater profitability. The didactic module of control of two variables designed and implemented with acquired knowledge in the career and knowledge based on research will reinforce theoretical – practices knowledge to the students of the Electromechanics career, La Maná extension through the control and interaction with flow and pressure variables. The student will be able to perform analyzed practices for the use of the module and in this way become more competitive in the industrial sector. The implemented didactic module has industrial elements such as: PLC-Inverter-Touch Panel-Pump-Pressure Transmitter. The Touch Panel allows interaction between the user and the variables to make Manual and Automatic controls. In manual mode, the parameters of frequency in the variator and position in the control valve are configured. In automatic mode, the control of the two variables is conducted through control strategies such as PID and On-Off.